Use Of the Quizizz Tool by Primary School Teachers: A Review of The Literature in Scopus from 2017-2023 - Torres-Díaz, Quetty Rosario; Cardoza-Sernaqué, Manuel Antonio; Montenegro-Camacho, Luis; Rivas-Mendoza, Milagros Isabel; Belleza-Torrejón, Sofía Emilce; García-Ventura, Cynthia Catherine (International Journal of Membrane Science and Technology, 2023)
The objective of this study was the analysis and quantification of the scientific literature by means of metrics in relation to the research consulted on the use of the Quizizz tool by primary education teachers during the period 2017-2023. Thus, the search was carried out through the combination of words "quizizz", "teachers". Likewise, the search filters were applied: Open access and the temporal criteria of 2017-2023, giving a total result of 45 studies that were exported in the Bibtex format for later reading with Cran-R. Among the results, it was identified that 2019 was the year with the highest scientific production with 10 studies. Regarding the productivity of authors, it was found that 2 authors have presented continuity with the topic studied. On the other hand, the relationship between the keywords of the author, the authors and the affiliations included was interpreted. The frequency of words showed that the keywords with the highest index are "motivation", "Online games", "quizizz", "Technology", "gamification", "assessment" and "online teaching - learning". The countries with the highest production are Indonesia and India. Word co-occurrence within the abstracts of all included studies was then analyzed with a sample of 100 words from all abstracts. The studies with the highest citation index present (n=130) and (n=90).